2007
DOI: 10.1007/s10653-006-9067-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of metal accumulation in deposited street dusts in Amman, Jordan

Abstract: Street dust samples (120 in total) were collected under stable weather conditions during the hot, dry season (August and September) of 2004 from six different localities (industrial, heavy traffic, medium traffic, light traffic, low traffic and rural) in greater Amman, the capital of Jordan. The concentrations of Fe, Cu, Cd, Pb, Zn and Ni in the dusts were determined by atomic absorption spectrophotometry. The high concentrations of Pb, Fe and Zn in the street dust samples were related to both anthropogenic (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(92 citation statements)
references
References 30 publications
6
83
0
3
Order By: Relevance
“…RDS from impervious surfaces is an important carrier of contaminants, often containing metals at elevated concentrations (Aryal et al, 2009;Xiang et al, 2010). Large amounts of pollutants, such as nutrients, metals, and hydrocarbons, are usually transported in RDS washoff (Sartor and Boyd, 1972;Huber and Dickinson, 1988;Al-Khashman, 2007). Quantifying the relationship between RDS and washoff particles in urban runoff could provide a new method for estimating the pollution load that a waterway receives (Herngren et al, 2005;Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…RDS from impervious surfaces is an important carrier of contaminants, often containing metals at elevated concentrations (Aryal et al, 2009;Xiang et al, 2010). Large amounts of pollutants, such as nutrients, metals, and hydrocarbons, are usually transported in RDS washoff (Sartor and Boyd, 1972;Huber and Dickinson, 1988;Al-Khashman, 2007). Quantifying the relationship between RDS and washoff particles in urban runoff could provide a new method for estimating the pollution load that a waterway receives (Herngren et al, 2005;Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the emission of heavy metals into the soil samples from the area surrounding the cement plant in the South of Jordan was demonstrated. The results showed that the mean concentration of Cr and Cd in 0-10 cm was 22.18 and 5 mg/kg, and at a depth of 10-20 cm was 6 and 2.18 mg/kg, respectively (24). Moreover, a research surveyed the pollution of soils by heavy metals in the area surrounding a cement plant and showed that the mean concentration of Cr and Cd was 83.2 and 0.9 mg/kg, respectively (24).…”
Section: Discussionmentioning
confidence: 97%
“…Metals in road dust result from traffic emissions (exhausts, oil lubricants, vehicle wear, brake lining, corroding building-material asphalts, automobile parts and yellow road paint degradation), industrial emission (smelters, incinerators, foundries and steel plants), as well as dry and wet deposition of atmospheric particulates [3,11,12]. In urban areas, traffic-related metal pollution in road dust is affected by vehicle type, traffic volume and behavior, soil parameters and meteorological conditions [3,12,13].…”
Section: Introductionmentioning
confidence: 99%